Analysis of Community Perspectives on the Development of Green Open Space to Support the Growth of MSMEs in Pagutan, Mataram City - Winda Maulia; Prayitno Basuki; Emi Salmah (Tinta Emas Publisher, 2024)
This research aims to determine the community's perspective on the development of Pagutan Green Open Space (RTH), Mataram City to support the growth of MSMEs. This research is a descriptive type of qualitative research. Determining the sample in this study used a purposive sampling technique. The location of this research is in Pagutan Green Open Space (RTH), Mataram City. Data collection procedures use observation, interviews and documentation. The validity of the data in this research uses triangulation of sources, techniques and time. Data analysis uses Miles and Huberman's interactive data analysis model which is divided into data collection, data reduction, data presentation, and drawing conclusions. The research results show that the majority of people's perspectives show that the development of Pagutan Green Open Space (RTH) has had a positive impact on the surrounding community in terms of employment, income, social and environmental indicators. This shows that the development of the Pagutan Green Open Space (RTH) has been utilized as well as possible by the community. Another impact resulting from the development of the Pagutan Green Open Space (RTH) is that MSMEs have the opportunity to develop and increase their income, which has an impact on their economic conditions.